Physicochemical and microstructural characteristics of Frafra potato (Solenostemon rotundifolius) starch - C. Osei Tutu; J.G.N. Amissah; J.N. Amissah; P.T. Akonor; W. Arthur; A.S. Budu; F.K. Saalia (International Journal of Food Properties, 2023)
Frafra potato (Solenostemon rotundifolius) is an underutilized climate-resilient tuber crop commonly cultivated in the tropics. Different accessions have been identified and bred to broaden its application in food. This study characterized the starches extracted from ten accessions, from Ghana (released) and Burkina Faso (unreleased), in terms of yield, physicochemical, and microstructural characteristics. The starches did not differ significantly (p < .05) in color (L*) and amount (35 to 39% dry matter basis). Furthermore, there were no significant differences (p < .05) among them in amylose/amylopectin ratio, syneresis %, granule types and shapes, except for one of the unreleased accessions (E82), which had a significantly (p < .05) smaller granule size. There were, however, significant differences (p < .05) in paste clarity of the starch gels, ranging from 51 to 63% of the starch gels, as well as in the thermal properties of the starches. The XRD and FTIR spectra showed the starches to be A-type, typical of tuber starches, with relative crystallinities ranging between 30.5 to 33.5%. The ten Frafra potato cultivars were clustered into two groups using PCA procedures; one group (Maa-Lana and Nutsugah) clustering on thermal properties of starch, while the other group (E82, E111, E132, E134, E145, Manga, Naachem-Tiir, and WAAPP) on paste clarity and change in temperature. The variations in granule size and thermal characteristics of the starches could impact the performance, cooking and textural properties, of these Frafra potato accessions in food applications.